A Novel Imidazole Derivative: Synthesis, Spectral Characterization, and DFT Study - Sapkota, Kamal Raj; Begam, Jahanara; Kumari, Shilpi (AMC Multidisciplinary Research Journal, 2025)
A novel Imidazole derivative, (E)-N-((1H-indol-7-yl) methylene)-5-phenyl-1H-imidazol-2-amine (IPA), was synthesized and characterized by elemental analysis, FT-IR, NMR, UV–Vis, and mass spectrometry. Spectral data confirmed the structure and purity of the compound. UV–Vis analysis showed π→π* and n→π* transitions, indicating strong conjugation. The molecular ion peak at m/z 286.12 verified its molecular weight. DFT study at the B3LYP/6-311G(d,p) level exhibits a HOMO–LUMO gap of 2.80 eV, in good agreement with the experimental value (2.70 eV), supporting its electronic structure and optoelectronic potential.